[18F]FDDNP PET binding predicts change in executive function in a pilot clinical trial of geriatric depression. (23rd February 2021) - Krause-Sorio, Beatrix; Siddarth, Prabha; Laird, Kelsey T.; Ercoli, Linda; Narr, Katherine; Barrio, Jorge R.; Small, Gary; Lavretsky, Helen
Abstract: Objectives: Geriatric depression often presents with memory and cognitive complaints that are associated with increased risk for Alzheimer's disease (AD). In a parent clinical trial of escitalopram combined with memantine or placebo for geriatric depression and subjective memory complaints, we found that memantine improved executive function and delayed recall performance at 12 months (NCT01902004). In this report, we used positron emission tomography (PET) to assess the relationship between in-vivo amyloid and tau brain biomarkers and clinical and cognitive treatment response. Design: In a randomized double-blind placebo-controlled trial, we measured 2-(1-6-[(2-[F18]fluoroethyl)(methyl)amino]-2-naphthylethylidene) malononitrile ([ 18 F]FDDNP) binding at baseline and assessed mood and cognitive performance at baseline, posttreatment (6 months), and naturalistic follow-up (12 months). Participants: Twenty-two older adults with major depressive disorder and subjective memory complaints completed PET scans and were included in this report. Results: Across both treatment groups, higher frontal lobe [ 18 F]FDDNP binding at baseline was associated with improvement in executive function at 6 months (corrected p = .045). This effect was no longer significant at 12 months (corrected p = .12). There was no association of regional [ 18 F]FDDNP binding with change in mood symptoms (corrected p = .2). Conclusions: [ 18 F]FDDNP binding may predict cognitive response to antidepressant treatment. Larger trials are required to further test the value of [ 18 F]FDDNP binding as a biomarker for cognitive improvement with antidepressant treatment in geriatric depression.